European Association of Urology (EAU) Prognostic Factor Risk Groups for Non-muscle-invasive Bladder Cancer (NMIBC) Incorporating the WHO 2004/2016 and WHO 1973 Classification Systems for Grade: An Update from the EAU NMIBC Guidelines Panel - Sylvester, Richard J; Rodríguez, Oscar; Hernández, Virginia; Turturica, Diana; Bauerová, Lenka; Bruins, Harman Max; Bründl, Johannes; van der Kwast, Theo H; Brisuda, Antonin; Rubio-Briones, José; Seles, Maximilian; Hentschel, Anouk E; et al. (European urology, 2021)
BACKGROUND: The European Association of Urology (EAU) prognostic factor risk groups for non-muscle-invasive bladder cancer (NMIBC) are used to provide recommendations for patient treatment after transurethral resection of bladder tumor (TURBT). They do not, however, take into account the widely used World Health Organization (WHO) 2004/2016 grading classification and are based on patients treated in the 1980s. OBJECTIVE: To update EAU prognostic factor risk groups using the WHO 1973 and 2004/2016 grading classifications and identify patients with the lowest and highest probabilities of progression. DESIGN, SETTING, AND PARTICIPANTS: Individual patient data for primary NMIBC patients were collected from the institutions of the members of the EAU NMIBC guidelines panel. INTERVENTION: Patients underwent TURBT followed by intravesical instillations at the physician's discretion. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Multivariable Cox proportional-hazards regression models were fitted to the primary endpoint, the time to progression to muscle-invasive disease or distant metastases. Patients were divided into four risk groups: low-, intermediate-, high-, and a new, very high-risk group. The probabilities of progression were estimated using Kaplan-Meier curves. RESULTS AND LIMITATIONS: A total of 3401 patients treated with TURBT ± intravesical chemotherapy were included. From the multivariable analyses, tumor stage, WHO 1973/2004-2016 grade, concomitant carcinoma in situ, number of tumors, tumor size, and age were used to form four risk groups for which the probability of progression at 5 yr varied from <1% to >40%. Limitations include the retrospective collection of data and the lack of central pathology review. CONCLUSIONS: This study provides updated EAU prognostic factor risk groups that can be used to inform patient treatment and follow-up. Incorporating the WHO 2004/2016 and 1973 grading classifications, a new, very high-risk group has been identified for which urologists should be prompt to assess and adapt their therapeutic strategy when necessary. PATIENT SUMMARY: The newly updated European Association of Urology prognostic factor risk groups for non-muscle-invasive bladder cancer provide an improved basis for recommending a patient's treatment and follow-up schedule.
Keywords: Neoplasm Invasiveness; Progression; WHO 1973 2004/2016; Retrospective Studies; nádory močového měchýře; Prognosis; Světová zdravotnická organizace; urologie; World Health Organization; Non–muscle-invasive bladder cancer; Prognostic factors; Guidelines; Risk groups; prognóza; retrospektivní studie; Humans; Urology; invazivní růst nádoru; Grade; Urinary Bladder Neoplasms; lidé